2011
DOI: 10.1159/000332223
|View full text |Cite
|
Sign up to set email alerts
|

The Oxford Classification of IgA Nephropathy: A Retrospective Analysis

Abstract: Background/Aims: The Oxford classification of IgA nephropathy (IgAN) assesses the presence of mesangial hypercellularity ≧50% (M1 vs. 0), endocapillary proliferation (E1 vs. 0), segmental glomerulosclerosis (S1 vs. 0), tubular atrophy/interstitial fibrosis >25 or 50% (T1 or 2 vs. 0), and has been reported as having prognostic value. We studied the clinical significance of the classification in our adult patients with IgAN. Methods: Retrospective study of 54 patients with biopsy-proven IgAN seen from 1983 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 50 publications
3
38
1
Order By: Relevance
“…These inconsistencies may be due to insufficient statistical power resulting from the small sample sizes of the studies. Like most previous studies, the present study failed to reveal a significant association of E with renal prognosis (15,18,36). Therefore, the variables included in our prediction rule would seem to be reasonable for application to research or clinical studies.…”
Section: Variables Scoressupporting
confidence: 51%
See 2 more Smart Citations
“…These inconsistencies may be due to insufficient statistical power resulting from the small sample sizes of the studies. Like most previous studies, the present study failed to reveal a significant association of E with renal prognosis (15,18,36). Therefore, the variables included in our prediction rule would seem to be reasonable for application to research or clinical studies.…”
Section: Variables Scoressupporting
confidence: 51%
“…In this study, M, S, and T were independently associated with renal outcome. T has been established as a significant prognostic factor associated with renal outcome in other studies, whereas the effects of M and S on renal prognosis have been inconsistent among studies (11,15,16,36). Some reports showed that M or S were not both selected as risk factors for future ESRD in multivariate analysis (15,16,36).…”
Section: Variables Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Other similar studies have been presented at the American Society of Nephrology's Renal Week 2010. A retrospective study from Chicago in 72 patients (16) and one from Korea in 181 patients (17) came to the conclusion that only tubulointerstitial fibrosis was predictive of outcome. Another study from Japan (18) emphasized on the importance of crescents, which were probably excluded from the Oxford study.…”
Section: Discussionmentioning
confidence: 99%
“…Previously Lee and Haas, have published a classifications method for IgAN (15)(16)(17)(18)(19)(20). The recent Oxford classification of IgAN assesses the presence of hypercellularity, proliferation in mesangial and endocapillary regions, segmental glomerulosclerosis and tubular atrophy/interstitial (MEST).Also it has been reported as having prognostic value (14,(21)(22)(23)(24). This classification method looked for reproducible pathological features that were correlated to renal survival independent of clinical features, rather than grouping patients into categories (24).…”
Section: Introductionmentioning
confidence: 99%